Cordycepin inhibits pancreatic cancer cell growth in vitro and in vivo via targeting FGFR2 and blocking ERK signaling - LI, Xue-Ying; TAO, Homng; JIN, Can; DU, Zhen-Yun; LIAO, Wen-Feng; TANG, Qing-Jiu; DING, Kan (Chinese journal of natural medicines, 2020)
Cordycepin (3′-deoxyadenosine) from Cordyceps militaris has been reported to have anti-tumor effects. However, the molecular target and mechanism underlying cordycepin impeding pancreatic cancer cell growth in vitro and in vivo remain vague. In this study, we reported functional target molecule of cordycepin which inhibited pancreatic cancer cells growth in vitro and in vivo. Cordycepin was confirmed to induce apoptosis by activating caspase-3, caspase-9 and cytochrome c. Further studies suggested that MAPK pathway was blocked by cordycepin via inhibiting the expression of Ras and the phosphorylation of Erk. Moreover, cordycepin caused S-phase arrest and DNA damage associated with activating Chk2 (checkpoint kinase 2) pathway and downregulating cyclin A2 and CDK2 phosphorylation. Very interestingly, we showed that cordycepin could bind to FGFR2 (KD = 7.77 × 10−9) very potently to inhibit pancreatic cancer cells growth by blocking Ras/ErK pathway. These results suggest that cordycepin could potentially be a leading compound which targeted FGFR2 to inhibit pancreatic cells growth by inducing cell apoptosis and causing cell cycle arrest via blocking FGFR/Ras/ERK signaling for anti-pancreatic cancer new drug development.